Lightsaber - Muhammad Noor, Ahmad Shukri (Universiti Putra Malaysia Press, 2017)
With the invention of the electricity bulb in the early 20th century, the world changed from the use of candlesticks and torch fires to a much more clean light. Since then, incandescent light bulbs were seen everywhere, ubiquitous for nearly half a century before the creation of fluorescent lamps.